Development of parameters for economic evaluation of using enrichment wastes of the mining enterprises - Федорченко, Анастасія Олександрівна; Попов, Станіслав Олегович (Technology audit and production reserves, 2016)
The problem of economic evaluation of use of enrichment wastes is investigated in the article. It is established a direct relation between the integrated use of mineral resources and increasing the efficiency of the mining enterprises. Improved economic evaluation of complex use of enrichment wastes of the mining enterprises is presented. The problem of complex use of enrichment wastes will always be important at every stage of economy (crisis or recession), as it provides significant savings of minerals and increase the economic efficiency of the mining enterprises. The model of using two types of concentrate production technology is presented: the main technology and through the optimal use of ore and enrichment wastes while minimizing costs. Organizational and economic mechanism for management of technology of integrated usage of enrichment wastes of the mining enterprises was developed. Selection of the most effective technology that will take effective decisions was chosen on the basis of this mechanism. The economic effect of introduction of the integrated use of mineral resources is 51,78 million UAH.